Case study on the effect continuous CO2 enrichment, via biogas scrubbing, has on biomass production and wastewater treatment in a high rate algal pond. (1st December 2019) - Young, Paul; Taylor, Michael J.; Buchanan, Neil; Lewis, Justin; Fallowfield, Howard J.
Abstract: Microalgae grown in high rate algal ponds (HRAP) treating wastewater are considered a promising feed for biofuel production. Biomass productivity is often considered to be limited by carbon availability, with the addition of CO2 being the proposed solution. Biogas from anaerobic wastewater treatment potentially provides a cheap, co-located CO2 source. Two identical 223 m 2 HRAPs were constructed at Melbourne Water's Western Treatment Plant, where biogas from an anaerobic lagoon is used to generate electricity. One HRAP was fed secondary treated wastewater that had been enriched with CO2 recovered from the biogas using industry standard biogas scrubbers, the Enriched HRAP, while the other HRAP was fed the same wastewater expect it had by passed the biogas scrubbers, the Control HRAP. The biomass production and wastewater treatment performance of the two HRAPs was compared over 12 months. The inlet to the Enriched HRAP had significantly higher free CO2 and inorganic carbon, 175.00 ± 49.30 mg L −1 and 110.00 ± 10.2 mg L −1, than the inlet to the Control HRAP, 9.30 ± 7.08 mg L −1 and 89.62 ± 5.12 mg L −1 . There were no significant differences in biomass production between the HRAPs as measured by dry matter, particulate organic carbon or nitrogen. Chlorophyll a was statistically higher in the Enriched HRAP, however, this measurement is potentially unreliable. Regarding wastewater treatment, only total nitrogen and ammonium removal differed significantly between the HRAPs, with the Control HRAP, 59.13 ± 21.13% and 76.46 ± 32.33%, slightly outperforming the Enriched HRAP, 53.52 ± 17.41% and 68.76 ± 31.17%. Overall, neither biomass production nor wastewater treatment was meaningfully improved by CO2 enrichment, however, wastewater treatment was still effective in both HRAPs. Graphical abstract: Image 1 Highlights: The most representative study on CO2 enrichment in high rate algal ponds (HRAP). The only large-scale HRAP wastewater CO2 enrichment study with an adequate control. Chlorophyll a was the only biomass measure that was increased in the Enriched HRAP. The Control HRAP had slightly increased mean removals for total N and NH4. The Enriched HRAP had slightly increased mean nitrate production.